Municipal Culture Incentive Law: what are their inclusive and democratic effects on local cultural production? - Xavier, Wescley Silva; Azevedo, Maria Aparecida Neves (Organizações & Sociedade, 2021)
This paper aims to analyze the inclusive and democratic effects of municipal cultural incentives law in Cataguases, Minas Gerais, fundamentally considering the promotion of citizenship and identity preservation based on cultural production. Data were collected through non-structured interviews with Cataguases cultural producers and analyzed according to a Marxist notion of discourse. Our findings revealed that approved purposes lead to a form of centralization on cultural production at the local level, characterized by the concentration of resources on established groups and the detachment from historically marginalized groups. Moreover, this scenario is aggravated when complementary cultural actions are transferred to the city’s cultural foundations, reinforcing the distinctive character of culture.